3a+6=-4a+2

Simple and best practice solution for 3a+6=-4a+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3a+6=-4a+2 equation:


Simplifying
3a + 6 = -4a + 2

Reorder the terms:
6 + 3a = -4a + 2

Reorder the terms:
6 + 3a = 2 + -4a

Solving
6 + 3a = 2 + -4a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '4a' to each side of the equation.
6 + 3a + 4a = 2 + -4a + 4a

Combine like terms: 3a + 4a = 7a
6 + 7a = 2 + -4a + 4a

Combine like terms: -4a + 4a = 0
6 + 7a = 2 + 0
6 + 7a = 2

Add '-6' to each side of the equation.
6 + -6 + 7a = 2 + -6

Combine like terms: 6 + -6 = 0
0 + 7a = 2 + -6
7a = 2 + -6

Combine like terms: 2 + -6 = -4
7a = -4

Divide each side by '7'.
a = -0.5714285714

Simplifying
a = -0.5714285714

See similar equations:

| 12x-21=28(4x-1) | | 12y^9/2y^11 | | 5-9/8x=6 | | X-4+4=-7 | | (y^2-x^2)dy+(2*x*y)dx=0 | | X-4+4=7 | | F(x)=-3(x+3)squared+3 | | 4+16x=10+15x | | 8x+-7=-2x+5 | | 10+3x-x-4=x | | 13x+17+34=90 | | 8x+1+9x-7=180 | | Z-6=z-4 | | -2x-7=32 | | (4+8)n=36 | | (4+8)n=3 | | 10x-14=-2x-13 | | 772x= | | 10x-14=2x+13 | | 5y+39+4x+6=180 | | x(x+2)=1295 | | 9x-15=-5x-16 | | 9x-15=5x+16 | | n-8+3=5 | | 8x+2=4(6x-9) | | 26=2x-8+4x | | 8x+2=4-(6x-9) | | .6(X+100)+.8X=109 | | 104=2x+2(x+4) | | .2x+7.9=6.6 | | 60-5x=6 | | 6x+9y+5x+2y= |

Equations solver categories